Blue Te Nanoneedles with Strong NIR Photothermal and Laser‐Enhanced Anticancer Effects as "All‐in‐One" Nanoagents for Synergistic Thermo‐Chemotherapy of Tumors. Issue 21 (30th August 2018) - Yu, Nuo; Li, Jinning; Wang, Zhaojie; Yang, Shuyan; Liu, Zixiao; Wang, Yanshu; Zhu, Meifang; Wang, Dengbin; Chen, Zhigang
Abstract: The conventional blue Te nanostructures exhibit strong photoabsorption in the near‐infrared (NIR) region but have ultralong lengths (tenths of micrometers), while purple Te nanostructures with short lengths (such as nanodots and nanorods) show extremely low intensity of the NIR band. These Te nanostructures cannot achieve simultaneously both the suitable size and high NIR absorption, undoubtedly hindering their bioapplication. Herein, blue Te nanoneedles are prepared through a facile one‐pot reduction route for the first time, and they have strong NIR absorbance while maintaining the shortened length (<500 nm). Compared to purple Te nanorods, blue Te nanoneedles have higher photothermal conversion efficiency using a 915 nm laser and exhibit laser‐enhanced antioxidative activity toward scavenging of free radicals. These blue nanoneedles show significant discrimination in cytotoxicity toward different cell‐lines, and demonstrate anticancer activity induced by mitochondrial dysfunction. Furthermore, when blue Te nanoneedles are injected in tumors of mice, tumors can be detected by thermal/photoacoustic imaging, and satisfactory therapeutic effects are achieved through the synergistic thermo‐chemotherapy in contrast to the limited therapeutic effect of Te‐alone treatment. Therefore, these blue Te nanoneedles can be served as a novel theranostic nanoagent for simultaneous multimodal imaging and synergistic thermo‐chemotherapy for tumors. Abstract : Blue Te nanoneedles are prepared through a facile one‐pot synthesis, and they have strong NIR absorbance while maintaining the shortened length. With excellent photothermal effect and high anticancer activity, blue Te nanoneedles can be served as novel theranostic nanoagents for simultaneous photoacoustic/thermal imaging and synergistic thermo‐chemotherapy for tumors.